Oral Hygiene and Maintenance Habits among PFM (Porcelain Fused to Metal) Fixed Partial Denture Wearers - Syeda Bakhtawar Hussain Shah, Ashar Hussain, Asad Baloch, Aisha Mehboob, Hafiz Mahmood Azam, Muhammad Siddique Qazi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Maintaining oral hygiene is crucial for the success and longevity of PFM fixed partial dentures (FPDs). However, poor hygiene practices can lead to complications such as plaque accumulation, gingival inflammation, and periodontal disease. This study aimed to evaluate oral hygiene habits, the role of dentists, and the use of special dental aids among PFM-FPD wearers. Aims: The primary aim was to assess oral hygiene practices, including cleaning underneath prostheses and general tooth brushing habits. Secondary objectives included evaluating the dentist's role in promoting hygiene and analyzing the usage and prescription of specialized dental aids. Methods: A cross-sectional study was conducted among 132 PFM-FPD wearers aged 25–50 years. Data were collected using structured questionnaires and clinical examinations. Parameters assessed included brushing habits, cleaning under prostheses, recall visits, use of special dental aids, and flossing practices. Statistical analysis was performed using SPSS software version 26. Results: 47.7% of respondents cleaned underneath their prosthesis, while 91.7% brushed their teeth regularly. Only 31.8% attended regular recall visits despite 88.6% receiving advice from dentists to do so. Special dental aids were used by 41.2% of respondents, with waxed floss being the most preferred type (60%). Lack of awareness regarding specific hygiene measures was evident among participants. Conclusion: The research shows that people who wear porcelain fused to metal FPD don't always take the time to brush and floss properly, thus there has to be more patient education and dentists working together to promote maintenance routines. Cleaning results may be greatly improved if more people are aware of the availability of specialist dental aids. Keywords: Oral hygiene habits, FPD, PFM, dentist role, flossing practices, dental